THE RIGHT TO WATER - Keturakienė, Airė (Teisė, 2017)
This article analysis the right to water. This right is a part of the progressive water resource management based on the balance of social, economic and environmental interests. The right to water entitles everyone to sufficient, safe, acceptable, physically accessible and affordable water to satisfy their basic needs.This article justifies the position that in the Republic of Lithuania the constitutional right to water could be deducted from the systematic interpretation of the constitutional norms ensuring the protection of environment, human health, human life and dignity. The article also claims that it is necessary to improve the definition of inhabitants’ right to use drinking water enshrined in the drinking water law and the legal procedures of disconnection of water supply for customers who do not settle their bills in due time.